Phenolic Content Analysis And Evaluation of Antinociceptive, Antioxidant, Anti-Inflammatory Potential of Alternanthera Pungens Kunth (Journal of Bangladesh Academy of Sciences, 2018)
The present study evaluated the analgesic, anti-inflammatory and antioxidant activities of Alternanthera pungens kunth.The ethanolic extract of Alternanthera pungens (EAP) showed analgesic effects by exerting ameliorated reaction time 40.79% and 44.74% at a dose of 250 and 500 mg/kg,respectively, whereas standard was 41.78%  by the hot plate test. Results of writhing inhibition were statistically significant (p